An outbreak of relapsing fever unmasked by microbial paleoserology, 16th century, France. Issue 4 (21st September 2020) - Oumarou Hama, Hamadou; Barbieri, Rémi; Guirou, Jacqueline; Chenal, Thomas; Mayer, Aurélie; Ardagna, Yann; Signoli, Michel; Aboudharam, Gérard; Raoult, Didier; Drancourt, Michel
Abstract: Objectives: Depicting past epidemics currently relies on DNA‐based detection of pathogens, an approach limited to pathogens with well‐preserved DNA sequences. We used paleoserology as a complementary approach detecting specific antibodies under a mini line‐blot format including positive and negative control antigens. Methods: Mini line blot assay incorporated skim milk as negative control, Staphylococcus aureus as positive control, and antigens prepared from lice‐borne pathogens Rickettsia prowazekii, Borrelia recurrentis, Bartonella quintana, and Yersinia pestis . Paleoserums were extracted from rehydrated dental pulp recovered from buried individuals. Mini line blots observed with the naked eye, were quantified using a scanner and appropriate software. Paleoserology was applied to the indirect detection of lice‐borne pathogens in seven skeletons exhumed from a 16th–17th century suspected military burial site (Auxi‐le‐Château); and 14 civils exhumed from a 5th–13th century burial site (Saint‐Mont). Direct detection of pathogens was performed using quantitative real‐time PCR. Results: In Auxi‐le‐Château, paleoserology yielded 7/7 interpretable paleoserums including 7/7 positives for B. recurrentis including one also positive for B. quintana . In Saint‐Mont, paleoserology yielded 8/14 interpretable paleoserums and none reacted against any of the four pathogens. Antibodies against R. prowazekii and Y. pestis were not detected. The seroprevalence was significantly higher in the military burial site of Auxi‐le‐Château than in the civil burial site of Saint‐Mont. Real‐time PCR detection of B. quintana yielded 5/21 positive (3 at Saint‐Mont and 2 at Auxi‐le‐Château) whereas B. recurrentis was not detected. Conclusions: Paleoserology unmasked an outbreak of relapsing B. recurrentis fever in one 16th – 17th century military garrison, missed by real‐time PCR. Paleoserology offers a new tool for investigating past epidemics, in complement to DNA sequence‐based approaches.